K.H. Abdul Wahid Hasyim's Thoughts on Islamic Education and Its Relevance to Islamic Education in Technological Times Islamic Education in Artificial Intelegence (AI) - Eka Supriatna; Ahmad Arifi; Ali Imran (Edumaspul: Jurnal Pendidikan, 2024)
This article aims to explore the biography and thoughts of KH. Abdul Wahid Hasyim in the field of Islamic education and its relevance to Islamic education in the contemporary era, especially in the era of artificial intelligence (AI) technology. This study uses a qualitative descriptive method with a literature study approach. The results of the study show that KH. Abdul Wahid Hasyim played a major role in the reform of Islamic education in Indonesia through visionary thinking and strategic steps. His thinking is relevant in the modern context by emphasizing the integration between religious education and general science. This is an inspiration for the transformation of Islamic education in the era of AI technology.